Legal Challenges for Digital Startup Development in Indonesia - I Nyoman Hendra Laksmana; I Putu Hendika Permana (Journal of Digital Law and Policy, 2023)
The high level of internet usage in Indonesia will certainly be in line with the growth of businesses that use the internet as their main part. Companies working on the Internet are known as digital startups. Digital Startup is a group of people who form an organization as a start-up company that produces products in the technology sector. Startups in Indonesia have been on the rise for at least the last decade. This phenomenon is also seen in Gojek and Tokopedia which are popular among Indonesians. With the rapid growth of startups, of course there are challenges to start and grow, one of which is legal challenges. From a legal point of view, in general startups experience problems such as employment relations, company forms, company names, licensing, intellectual property issues and, contracts. Before starting a business, startup business people must thoroughly study the Indonesian laws and regulations governing startup businesses, as well as study the obstacles that will be faced when starting and running their business activities. So that the risk of failure in running a startup business can be minimized. So in this study the researchers analyzed the legal challenges that need to be prepared to be able to build a digital startup. In this study, researchers used a qualitative approach to collect data and utilize all the information on the subject matter. so that 7 important legal challenges can be found and need to be prepared to be able to build a digital startup. The 7 challenges include: Regulations, Legal Entities or Business Entities, Licensing, Protection of Business Competition, Financial Transactions, Crowdfunding, and Venture Capital.